Nulla su di noi senza di noi Una ricerca empirica sull'abilismo in Italia - Bellacicco, Rosa (Percorsi di ricerca, 2022)
In Italy, the term ableism is not commonly used in everyday language and is even less present in public debate compared to other forms of discrimination such as sexism or racism. However, ableism manifests very often in our society, generating inequalities, micro-aggressions, and social exclusion. This book presents the first empirical research regarding ableism in Italy, adopting an intersectional perspective on its relations with other forms of discrimination (sexism, classism, racism, etc.). Following the motto "Nothing about us without us", the research was conducted with a group of people with disabilities. The book has both an educational and scientific purpose. Firstly, it discusses the multiple manifestations of ableism and its consequences theoretically. Secondly, it describes the participatory research process aimed at developing a scale to identify ableist attitudes. Thirdly, it presents the results of a questionnaire on ableism and intersectionality, involving a representative sample of Italian adults. Lastly, it describes the discrimination experienced by people with disabilities in relation to multiple life areas (e.g., mobility, communication, sport, independent living) from the perspective of the research participants.